The lived experiences of demotivated 10th-graders speaking in english classes after pandemic: a phenomenological study (2023)
Motivation is the desire of a student to acquire new knowledge and put it into practice by performing tasks. It plays an essential role in students when learning a foreign language. However, the COVID-19 pandemic has harmed foreign language learners' motivation to participate in oral activities in English. The purpose of this phenomenological study was to understand the lived experiences of 10th-grade students that reflected their demotivation to participate in speaking activities after the COVID-19 pandemic. This study employs Giorgi's five-step method for conducting a phenomenological analysis. The data sources for this research included in-depth interviews and researchers’ diary. Four themes emerged from the data collected: 1) The bright side of motivation, 2) The battle between the heart and the brain, 3) The barriers of communication in foreign language learning, and 4) Awareness of a duality in teaching. The study highlights the importance of motivation in foreign language learning and in the development of speaking skills.